Graphene versus Multi-Walled Carbon Nanotubes for Electrochemical Glucose Biosensing - Edmond Lam (Materials, 2013)
: A simple procedure was developed for the fabrication of electrochemical glucose biosensors using glucose oxidase (GOx), with graphene or multi-walled carbon nanotubes (MWCNTs). Graphene and MWCNTs were dispersed in 0.25% 3-aminopropyltriethoxysilane (APTES) and drop cast on 1% KOH-pre-treated glassy carbon electrodes (GCEs). The EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide)-activated GOx was then bound covalently on the graphene- or MWCNT-modified GCE. Both the graphene- and MWCNT-based biosensors detected the entire pathophysiological range of blood glucose in humans, 1.4–27.9 mM. However, the direct electron transfer (DET) between GOx and the modified GCE’s surface was only observed for the MWCNT-based biosensor. The MWCNT-based glucose biosensor also provided over a four-fold higher current signal than its graphene counterpart. Several interfering substances, including drug metabolites, provoked negligible interference at pathological levels for both the MWCNT- and graphene-based biosensors. However, the former was more prone to interfering substances and drug metabolites at extremely pathological concentrations than its graphene counterpart.